Social interactions in museums: the role of mediators in family visits to the Galeria da Biodiversidade (Oporto, Portugal) - Massarani, Luisa; Cândido-Vendrasco, Natália; Luis, Cristina; Portela, Antero (Arte, Individuo y Sociedad, 2026)
Mediators in science museums have the potential to create experiences and learning beyond what is possible in exhibits alone. However, there is still little empirical research to help us understand and improve facilitation practices and mediation models in museums, particularly in unstructured interactions, which are most common in family visits. In this study, we address this issue by exploring different mediation models performed by mediators during the visits of five family groups at the Galeria da Biodiversidade, in Portugal. The study has a descriptive qualitative approach, specifically a multiple case study. For data collection we used audiovisual recordings generated with a GoPro installed in one of the children of each family and, as an analysis tool, we used a protocol for the identification of relevant aspects for the articulation of mediation models. The results show the important role that mediators play during the visit. However, they suggest that the visitor-centered mediation model is still the least used, prevailing models that offer less learning opportunities for the visiting public.
Keywords: Mediators; mediation models; science museums; family visits